Fertilization with monoammonium phosphate in the production of Formosa ‘Tainung-01’ papaya in the potiguar semiarid - Tosta, Mauro da Silva; Almeida, João Paulo Nobre de; Leite, Grazianny Andrade; Fonseca Neto, Joacy; Mendonça, Vander; Freitas, Poliana Samara Castro (Comunicata Scientiae, 2019)
The achievement of good productivity and quality of fruits is directly associated with a balanced fertilization, in which phosphate fertilizers have an important role in the agricultural production system. In this context, this work aimed to evaluate the effect of doses of monoammonium phosphate in ground fertilization and associated with the topdressing in the production of the Formosa “Tainung-01” papaya. The experimental design was in complete randomized blocks, in an split plots outline, having as main factor four fertilizer doses in ground fertilization (0; 80; 160, and 250 kg ha-1 of monoammonium phosphate [MAP]) and, as a sub-portion, two fertilizers in topdressing (20 kg ha-1 of Cosmofert® + 45 kg ha-1 of MAP” and “90 kg ha-1 of MAP). The harvesting began in the eighth month and extended until the 12th month after transplanting of the seedlings. All fruits of five plants per experimental unit were collected and classified. The number of fruits, the production per plant, the yield, and the percentage of marketable fruits were evaluated. The ground fertilization with the monoammonium phosphate did not influence the production of Formosa 'Tainung-01' papaya fruits exclusively destined to the domestic market. When the production is destined to the external market, a dosage of 74.0 kg ha-1 of monoammonium phosphate can be used in ground fertilization.